2012
DOI: 10.1117/1.jei.21.1.010901
|View full text |Cite
|
Sign up to set email alerts
|

Heart chambers and whole heart segmentation techniques: review

Abstract: Abstract. Computer-aided segmentation of cardiac images obtained by various modalities plays an important role and is a prerequisite for a wide range of cardiac applications by facilitating the delineation of anatomical regions of interest. Numerous computerized methods have been developed to tackle this problem. Recent studies employ sophisticated techniques using available cues from cardiac anatomy such as geometry, visual appearance, and prior knowledge. In addition, new minimization and computational metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 191 publications
0
35
0
Order By: Relevance
“…Compared with other imaging modalities (such as ultrasound and magnetic resonance imaging), cardiac computed tomography (CT) can provide detailed anatomical information about the heart chambers, great vessels, and coronary arteries [4,5]. Actually, CT is often preferred by diagnosticians since it provides more accurate anatomical information about the visualized structures, thanks to its higher signal-to-noise ratio and better spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other imaging modalities (such as ultrasound and magnetic resonance imaging), cardiac computed tomography (CT) can provide detailed anatomical information about the heart chambers, great vessels, and coronary arteries [4,5]. Actually, CT is often preferred by diagnosticians since it provides more accurate anatomical information about the visualized structures, thanks to its higher signal-to-noise ratio and better spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…These works deal with different strategies for approaching the segmentation task, including image-driven algorithms [10][11][12][13], probabilistic atlases [14,15], fuzzy clustering [16], deformable models [17][18][19], neural networks [20], active appearance models [21,22], anatomical-based landmarks [23], or level set and its variations [24,25]. A comprehensive review of techniques commonly used in cardiac image segmentation can be found in Kang et al [5]. Nevertheless, many published methods have various disadvantages for routine clinical practice: they are either computationally demanding [6,14,16,22], potentially unstable for subjects with pathology [25,26], limited to the left ventricle [11,24,25,27], require additional images to be acquired [28,29], or need complex shape and/or gray-level appearance models constructed (or 'learned') from many manually segmented images -which is labor intensive and of limited use due to both anatomical and image contrast inconsistencies [14,22,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Automatic image segmentation techniques [32,33] could be explored to speed up the manual segmentation process. Other segmentation techniques such as shape-based interpolation [34] and superresolution [35,36] can also be potentially used to automate and increase the accuracy of the cardiac segmentation.…”
Section: Limitationsmentioning
confidence: 99%
“…and 1 In the literature, several approaches (e.g., [16] [17]) have been proposed to segment the cardiac images by using time constrained information. In [16], the authors introduced prior motion knowledge for the contour deformation through temporal smoothing (average of two adjacent frames) or trajectory constraints (to constrain the shape to its reference trajectory).…”
Section: A Snakementioning
confidence: 99%
“…We refer the reader to the two recently published survey papers [1] and [2] for detailed reviews on the topic. In contrast, due to its higher anatomical complexity, the right ventricle (RV) segmentation has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%